2020
DOI: 10.1097/qad.0000000000002412
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E is an effective treatment for nonalcoholic steatohepatitis in HIV mono-infected patients

Abstract: Objective: HIV-infected patients are at increased risk of nonalcoholic steatohepatitis (NASH). Vitamin E is recommended for treatment of NASH in the general population. However, its safety and efficacy among HIV-infected patients remain unknown. Design: Single-centre, phase IV, open-label, single arm clinical trial. Methods: HIV mono-infected patients without significant alcohol intake or viral hepatitis coi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 37 publications
3
21
0
Order By: Relevance
“…At present, vitamin E treatment may be considered as a bridge therapy only, while waiting for availability of new drug combinations simultaneously addressing steatosis and fibrosis (Table 3). ( 38 )…”
Section: Current Trials For Nash In Hivmentioning
confidence: 99%
“…At present, vitamin E treatment may be considered as a bridge therapy only, while waiting for availability of new drug combinations simultaneously addressing steatosis and fibrosis (Table 3). ( 38 )…”
Section: Current Trials For Nash In Hivmentioning
confidence: 99%
“…Although tesamorelin was well tolerated with no overall change in fasting glucose or HbA1c, there were still two study discontinuations in the tesamorelin group due to hyperglycemia 19 . Another trial showed that 24 weeks of vitamin E treatment decreased ALT and the degree of hepatic steatosis in HIV mono‐infected patients with non‐alcoholic steatohepatitis and showed no change in triglycerides, total cholesterol, HDL cholesterol, and HOMA‐IR 20 . Nevertheless, a randomized controlled trial of statin versus placebo, 147 HIV‐infected individuals with 96‐week follow‐up had hepatic steatosis increased over time, regardless of statin treatment 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies with 27 HIV patients with NASH reported that vitamin E supplementation was a most effective treatment as it has enhanced the ALT level, ck-18 and CAP score. Moreover, it does not cause any adverse effects in participated individuals [59].…”
Section: Human Immunodeficiency Virusmentioning
confidence: 92%